The historical reliability of the New Testament : countering the challenges to evangelical Christian beliefs - Blomberg, Craig L., 1955-; Stewart, Robert B. (Nashville : B & H Academic, 2016)
Questions about the reliability of the New Testament come from many directions today. This volume addresses all of the most common ones, including the transmission of the text, the choice of books for the canon, the formation of the Gospels, the supposed contradictions among parallels, a comparison of Jesus and Paul and another of Acts and Paul, proposals of pseudonymity for various letters, and even the value of the book of Revelation. Selected historical corroborations of details from all parts of the New Testament are also presented. A chapter on the unique problems associated with miracles rounds out the volume. This book is a fully stocked toolbox for anyone interested in whether we can still trust the New Testament in the twenty-first century. Blomberg answers the question with a ringing affirmative. --
Part 1. The Synoptic Gospels. The formation of the Synoptic Gospels ; Contradictions among the Synoptics? ; Corroboration of the Synoptics -- Part 2. The Gospel of John. The formation of the Gospel of John ; Evidence for the accuracy of John --Part 3. Acts and Paul. The credibility of Acts ; Paul in Acts and in the Epistles ; Forgeries among the Epistles of Paul? ; Is Paul the true founder of Christianity? -- Part 4. The rest of the New Testament. The non-Pauline epistles: New Testament anomalies? ; The Book of Revelation: are historical matters even relevant? --Ppart 5. Canonicity and transmission. The Nag Hammadi literature and New Testament Apocrypha ; Textual transmission and the formation of the Canon --Part 6. The problem of miracles. Miracles in the New Testament world and today.
Includes bibliographical references and indexes.
Keywords: Bible. -- Evidences, authority, etc; Bible. -- Canon; Bible- New Testament -- Evidences